Asthma Education, Action Plans, Psychosocial Issues and Adherence - John Kolbe (Canadian Respiratory Journal)
This article deals with four separate but not disparate topics. The first section discusses asthma education, reviews the current literature and attempts to challenge some of the dogma that is associated with this area. Knowledge alone does not guarantee appropriate behaviour, due to a variety of adverse socioeconomic and psychological factors that need to be considered for each patient. Action plans and peak flow monitoring have both been disappointing in terms of reducing asthma morbidity; the former needs to be individualized, and the latter may be useful in specific situations. Space precludes an in-depth discussion of psychological issues and adherence, but an attempt has been made to address salient issues, particularly related to the first two topics. Psychological factors, especially anxiety, play an important role in asthma outcome. Adherence to medication prescriptions and other management strategies need to be taken into account when an individual’s treatment program is planned.